A new simple structure PLL for both single and three phase applications. (January 2016) - Ahmad, Ahmad Ale; Pichan, Mohammad; Abrishamifar, Adib
Highlights: A new phase locked loop (PLL) is proposed based on new orthogonal signal estimator and simple structure VCO. The proposed PLL is robust against input signal distortion such as harmonic polluted and amplitude collapse. The proposed PLL is applicable for both single and three phase systems. The proposed PLL has a simple structure for practical application. Abstract: In this paper, a new phase locked loop (PLL) is proposed for both single and three phase systems. A Phase detection is the most challenging issue in single phase PLLs. Due to the benefits of vector multiplier phase detector, new orthogonal signal estimator is proposed with the help of simple VCO to make the vector multiplier PD usable for single phase PLLs. The proposed PLL shows fast dynamic response and robust performance against input signal distortion such as harmonic polluted and amplitude collapse. Also, it has a simple structure and less computational burden which make it easy for fully digital implementation. The proposed PLL is implemented digitally based on a TMS320F28335 developed board. To fully evaluate the performance of proposed PLL, a 4 kW single phase grid connected converter is also provided. All the simulation and experimental results verify the effectiveness and superior performance of the proposed PLL.